Gallstone Ileus Treated by Incidental Meckel’s Diverticulectomy - Koenig, Zachary A; Turner, Jason (Curēus (Palo Alto, CA), 2021)
Gallstone ileus is an uncommon cause of intestinal obstruction in the elderly. It is typically recognized on computed tomography by the presence of pneumobilia and a gallstone in the right iliac fossa. Nonetheless, it is important to consider that gallstone ileus may represent the presentation of another pathology rather than an entity on its own. Here, we report successful retrieval of a gallstone that was causing ileus. Intraoperatively, the gallstone was noted lodged in the terminal ileum distal to an incidentally noted Meckel's diverticulum. The gallstone was milked proximally into the Meckel's diverticulum and the base was transected. This case illustrates a rare, but unique, surgical technique utilizing a small bowel diverticulum as a vector for stone removal.